Factors influencing motivation and behaviour in utilising pharmacy information system among pharmaceutical staff in Malaysia / Cenysia Joimur - Cenysia , Joimur (2022)
The study has been performed in order to evaluate the factors influencing motivation and behavioural intention in using the Pharmacy Information System (PhIS) that has been conducted among Pharmaceutical Staff in Public Healthcare in Malaysia. PhIS has been developed after previous Hospital Information System (HIS) in Malaysia but there were several issues after the implementation of HIS including the resistant and negative thinking due to the unexpected performance occurred after the system implementation. Thus, the study has been conducted in order to evaluate the factors influencing towards users’ motivation and behavioural intention during the training session of the current system of PhIS. The research was using quantitative data and about 500 questionnaires have been distributed and collected among the Public Pharmaceutical Staff in Malaysia. However, according to the sample size needed, there were 310 respondents selected. These respondents selected among the Pharmaceutical Staff of Public Healthcare in Peninsular and East Malaysia to whom attended and represented their departments during the training. Based on the finding and analysis conducted, there were significant relationship between the teaching presence, cognitive presence and social presence. Each aspect in the study has been indicated positive relationship with each other in regards to the respondents’ perception, motivation and behavioural intention in using the system. Only minority who were not agreed to the benefit of using PhIS in their workplace. It draws the conclusion that the respondents have shown motivation in using the system after the training conducted despite of the resistance attitude towards the implementation of the previous system. In the study, the PhIS users at the Government’s Hospitals and Clinics in Malaysia show encourage feedback after the teaching, cognitive and social